Investigating 3D spatial units’ types as basis for refined 3D spatial profiles in the context of LADM revision - Kalogianni, E. (2020)
The aim of this paper is to investigate, examine and review - in the context of LADM revision- the different types of real-world spatial units, as they have initially been organised by Thompson et al (2015). Based on the revised taxonomy, spatial profiles for the spatial units’ categories are introduced and (several) are further explored and designed Hence, the focus on this paper lies on two levels: the taxonomy and the spatial profiles, while the level of encoding is not included in the scope of this paper. However, the investigation of the technical encodings that will be used for the implementation of the 3D spatial profiles is introduced at the paper as future work, underlying its importance. Within this concept, the scope and ambition of LADM revision are discussed.